Situation Report: Hungary, 27 July 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungarian Interest in Proposed Nixon Visit to China Italian CP Delegation in Budapest Reorganization of Hungarian Banking System Expansion of Economic Relations with Canada University Entrance Examinations End Problems of Hungarian Agriculture More Profitable Cattle Breeding